A Library for Libraries: Is the Joint Library Facility becoming an Interlibrary Loan Hub for Libraries?. Issue 2 (6th March 2017) - van Duinkerken, Wyoma; Hartnett, Eric; Algenio, Emilie
ABSTRACT: What happens when libraries begin to use ILL to request items that they already own in their home collection? The goal of this multiyear study involving 9565 ILL requests to the Joint Library Facility in Bryan, Texas, is to examine whether or not the shared storage facility was becoming an ILL hub for some libraries. This paper reports the results of the study and how individual requesting and lending interlibrary loan policies and procedures might be altered to address these developing issues.